2009
DOI: 10.1007/s10295-009-0559-2
|View full text |Cite
|
Sign up to set email alerts
|

Neochloris oleabundans UTEX #1185: a suitable renewable lipid source for biofuel production

Abstract: Energy crises, global warming, and climatic changes call for technological and commercial advances in manufacturing high-quality transportation fuels from unconventional feedstocks. Microalgae is one of the most promising sources of biofuels due to the high yields attained per unit area and because it does not displace food crops. Neochloris oleabundans (Neo) microalga is an important promising microbial source of single-cell oil (SCO). Different experimental growth and lipid production conditions were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
0
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(107 citation statements)
references
References 13 publications
5
94
0
8
Order By: Relevance
“…The N. conjuncta grown in Bristol medium was found to have a lipid content (1.07 +/− 0.4 g lipid/g dry biomass) significantly (p = 0.0004) higher than any other species/medium combination, which ranged from 0.5 to 50 g lipid/g dry biomass. These values agree with the 0.27 (Sun et al, 2014), 0.50 (Griffiths et al, 2012), and 0.52 (Gouveia et al, 2009) g lipid/g dry biomass reported for N. oleoabundans.…”
Section: Lipid Production and Productivitysupporting
confidence: 91%
“…The N. conjuncta grown in Bristol medium was found to have a lipid content (1.07 +/− 0.4 g lipid/g dry biomass) significantly (p = 0.0004) higher than any other species/medium combination, which ranged from 0.5 to 50 g lipid/g dry biomass. These values agree with the 0.27 (Sun et al, 2014), 0.50 (Griffiths et al, 2012), and 0.52 (Gouveia et al, 2009) g lipid/g dry biomass reported for N. oleoabundans.…”
Section: Lipid Production and Productivitysupporting
confidence: 91%
“…The accuracy of these empirical equations in estimating the quality of biodiesel has been previously shown (Ramos et al, 2009;Hoekman et al, 2012). Moreover, measured values and calculated values by these equations in green algae C. protothecoides (Xu et al, 2006), Neochloris oleabundans (Gouveia et al, 2009) and S. obliquus (Abd El Baky et al, 2012) were compared prior to this study, and results indicated that the values from equations of Song et al (2014) were very close to the measured values. Thus, the biodiesel property in this study, the degree of unsaturation (DU), kinematic viscosity (KS), specific gravity (SG), cloud point (CP), iodine value (IV), cetane number (CN) and higher heating value (HHV) were determined by empirical equations from FA composition as described by Song et al (2014), while cold filter plugging point (CFPP) by Nascimento et al (2013).…”
supporting
confidence: 54%
“…Moreover, lipid content, fatty acid profile, and acid value are also important parameters of biofuel (Gouveia et al 2009). It is known that lipid production by microalgae is regulated by environmental factors (Harwood and Jones 1989).…”
Section: Introductionmentioning
confidence: 99%